Students in Turkey during the early days of the COVID-19 pandemic - ÇAĞLAYAN AKAY, EBRU; DUMLUDAĞ, DEVRİM; ZÜLFÜOĞLU, ÖZKAN; BÜLBÜL, HOŞENG (My University, 2022)
This study aims to analyse the subjective well-being of university students during the early days of the COVID-19 pandemic process and to examine how students have been afected economically, psychologically and socially. Other subjects included in the scope of the study are the suitability of the physical conditions during the process of online education, the students’ motivation, and their expectations towards the future. The study also analyses the connection between these factors and the subjective well-being concepts of happiness and life satisfaction. The study focuses on students of the Faculty of Economics at Marmara University in Turkey. In total, 428 students took part in the survey prepared for the study. Descriptive analyses indicate that students have been negatively afected in terms of psychological and socio-economic factors along with subjective well-being. Ordered probit models show a statistically signifcant relationship between a major part of these changes and subjective well-being variables
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Happiness; Life satisfaction; Student; Covid-19